A Companion to the literature and culture of the American west - Witschi, Nicolas S. 1966- (Chichester, West Sussex, United Kingdom Wiley-Blackwell, 2011)
"Few geographical regions of the United States have been more glamorized, mythologized -- and misunderstood -- than the American west. A Companion to the Literature and Culture of the American West presents an in depth and highly detailed exploration of historic and contemporary cultural expressions rooted in America's western states. Historically and culturally, the west exhibits a richness and depth of cultural expression that is often at odds with the popular imagery. Divided into three thematic sections, the companion offers a series of illuminating essays by literary and cultural scholars to reveal the complexity of the many "wests" in our imagination and reality. The first section considers the west chiefly through a historical lens, both literary and cultural, exploring such topics as exploration and Gold Rush narratives, women's writings, the growth of suburbs, class and postcolonial perspectives, and the myriad of cultural expressions from many of the west's sub-regions and population groups. The chapters in the second section present a more genre-based approach, interpreting such topics as pictorial art, cinema, cowboy poetry, autobiography, nature writing, and detective fiction. In the final part, closer, more sustained readings of specific cases illuminate some of the west's persistent questions and issues, including those related to identity, performance, representation, and marketing. A Companion to the Literature and Culture of the American West offers a fully realized portrait of the depth and complexity of cultural expressions that continue to emerge from the American west"--Provided by publisher.
Table of contents : Acknowledgments. -- Note on Contributors. -- List of Illustrations -- Part I: Introduction. -- 1 Imagining The West (Nicolas S. Witschi). -- Part II: Regions and Histories. -- 2 Exploration, Trading, Trapping, Travel, and Early Fiction, 1780-1850 (Edward Watts). -- 3 Worlds of Wonder and Ambition: Gold Rush California and the Culture of Mining Bonanzas in the North American West (Peter Blodgett). -- 4 The Literate West of Nineteenth-Century Periodicals (Tara Penry). -- 5 A History of American Women's Western Books, 1833-1928 (Nina Baym). -- 6 Literary Cultures of the American Southwest (Daniel Worden). -- 7 Literary Cartography of the Great Plains (Susan Naremore Maher). -- 8 The Literary Northern Rockies as The Last Best Place (O. Alan Weltzien). -- 9 North by Northwest: The Last Frontier of Western Literature (Eric Heyne). -- 10 Chronotopes of the Asian American West (Hsuan L. Hsu). -- 11 African American Literature and Culture and the American West (Michael K. Johnson). -- 12 Mythical Frontiers: Manifest Destiny, Aztlâan, and the Cosmic Race (John L. Escobedo). -- 13 Native American Literature and Culture of the American West (Kathleen Washburn). -- 14 Framing Class in the Rural West: Cowboys, Double-Wides and McMansions (Nancy Cook). -- 15 Postcolonial West (Alex Hunt). -- 16 New West, Urban and Suburban Spaces, Postwest (Krista Comer). -- Part III: Varieties and Forms. -- 17 What We Talk about When We Talk about Western Art (Brian W. Dippie). -- 18 "All Hat and No Cattle": Romance, Realism, and Late-19th-Century Western American Fiction (Gary Scharnhorst). -- 19 The Coyote Nature of Cowboy Poetry (Barbara Barney Nelson). -- 20 "The Wind Blew Them Away": Folksinging the West, 1880-1930 (David Fenimore). -- 21 Autobiography (Gioia Woods). -- 22 Housing the American West: Western Women's Literature, Early Twentieth Century and Beyond (Cathryn Halverson). -- 23 The Apple Doesn't Fall Far from the Tree: Western American Literature and Environmental Literary Criticism (Hal Crimmel). -- 24 Detective Fiction (Nicolas S. Witschi). -- 25 The American Western Film (Corey Creekmur). -- 26 Post-Western Cinema (Neil Campbell). -- Part IV: Issues, Themes, Case Studies. -- 27 America Unscripted: Performing the Wild West (Jefferson Slagle). -- 28 Revising Public Memory in the American West: Native American Performance in the Ramona Outdoor Play (Karen E. Ramirez). -- 29 Omnimedia Marketing: The Case of The Lone Ranger (Chadwick Allen). -- 30 The Nuclear Southwest (Audrey Goodman). -- 31 Ranging Over Stegner's Arid West: Mobility as Adaptive Strategy (Bonney MacDonald). -- 32 The Global West: Temporality, Spatial Politics, and Literary Production (Susan Kollin). -- 33 Tumbling Dice: The Problem of Las Vegas (Stephen Tatum and Nathaniel Lewis).
Includes bibliographical references and index.
Keywords: American literature -- History and criticism; West (U.S.) -- In literature; West (U.S.) -- In mass media; West (U.S.) -- In art